International outsourcing and the skill structure of labour demand in the United Kingdom - Alexander Hijzen; Holger Görg; Robert C. Hine (Institute for the Study of Labor (IZA), 2004)
This paper investigates empirically the link between international outsourcing and the skill structure of labour demand in the United Kingdom. It is the first detailed study of this issue for the UK. Outsourcing is calculated using import-use matrices of input-output tables for manufacturing industries for the period 1982 to 1996. Estimating a system of variable factor demands, our main results show that international outsourcing has had a strong negative impact on the demand for unskilled labour. Hence, international outsourcing is an important component in explanations of the changing skill structure of manufacturing industries in the United Kingdom.
Keywords: F14; J31; 330; Outsourcing; fragmentation; trade; wages; skill-biased technological change; Outsourcing; Qualifikation; Arbeitsnachfrage; Facharbeiter; Ungelernte Arbeitskräfte; Großbritannien